Protective effects of Hammada scoparia flavonoid-enriched fraction on liver injury induced by warm ischemia/reperfusion. (December 2015) - Saidi, Saber Abdelkader; Bourogâa, Ezzeddine; Bouaziz, Amira; Mongi, Saaoudi; Chaaben, Rim; Jamoussi, Kamel; Mezghani-Jarraya, Raoudha; van Pelt, Jos; El-Feki, Abdelfattah
Abstract Context: Hepatic ischemia/reperfusion injury (IRI) is a major cause of liver damage during liver surgery and transplantation. Plants have historically been used in treating liver damage, and Hammada scoparia (Pomel) (Chenopodiaceae) has been reported to possess a broad spectrum of pharmacological and therapeutic activities. Objective: In this study, a flavonoid-enriched fraction was used before the warm ischemia (WI) process as pharmacological preconditioning and in combination with technical postconditioning to evaluate their protective effects. Materials and methods: The rats were divided into five groups: a sham group; a control group (Control-IR) that was submitted to 60 min WI; a Pharmacological Preconditioning group (PreC-IR) that received flavonoid-enriched fraction (200 mg/kg body weight); a Postconditioning group (PostC) and a PreC + PostC group. Results: The use of the flavonoid-enriched fraction was noted to significantly (p < 0.05) reduce liver injury, as evidenced by the decrease in liver transaminase activities (AST and ALT) and lactic dehydrogenase (LDH), alkaline phosphatase (ALP), and lipid peroxidation (TBARS), levels as well as the enhancement of antioxidant enzymes (catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx)) responses. The results also indicated that, compared with the separate application of pharmacological preconditioning and postconditioning, the combination of both treatments was more effective in reducing tissue oxidative stress levels through modulating SOD, GSH-PX, and CAT activities. Furthermore, the combined protocol further decreased the liver morphological score compared with solo treatment. Discussion and conclusion: Overall, the results indicate that the H. scoparia flavonoid-enriched fraction could be a promising candidate for future application as a pharmacological preconditioning agent against hepatic IRI.